The Development of Early Sunnite ḥadīth Criticism : The Taqdima of Ibn Abī ḥātim al-Rāzī (240/854-327/938) - Dickinson, Eerik (Brill Book Archive Part 1, ISBN: 9789004472495., 2001)
ḥadīth are the documents recording the words and actions of the Prophet Muḥammad. Originally an enormous and amorphous corpus, Muslim scholars of the third/ninth century separated the ḥadīth they regarded as true from those they held to be forgeries, producing collection of ḥadīth which still command the respect of Muslims today. Ibn Abī ḥātim al-Rāzī (240/854-327/938) was one of the most prominent exponents and practitioners of ḥadīth criticism. He left a copious written legacy, including his famous Taqdima , a biographical dictionary of the early ḥadīth critics. The Taqdima reveals Ibn Abī ḥātims's vision of the critic and gives insight into the mechanism of ḥadīth criticism. It also provides a platform for the examination of the basic intellectual orientation of the ḥadīth critics and their conflicts with their opponents.